Load settlement characteristics of a piled raft in sand - Seet, Kelvin Chee Kiong. (2010)
Raft foundations have been commonly employed as foundations to overcome differential settlements due to erratic soil conditions and close proximity of pile caps. The bearing capacity requirement is usually fulfilled due to the large area coverage by the raft foundation. However raft foundations may settle excessively in weak or compressible soils and the most cost effective method to reduce settlement is to introduce piles.